2010
DOI: 10.1536/ihj.51.159
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Atrial Repolarization and Depolarization Contribute to the Inducibility of Atrial Fibrillation in Brugada Syndrome

Abstract: SummaryBrugada syndrome is often accompanied by atrial tachyarrhythmia, such as atrial fibrillation (AF). The aim of this study was to examine atrial vulnerability in patients with Brugada syndrome. Two groups of patients were compared: 18 patients with Brugada syndrome (Brugada syndrome group) and 11 age-matched patients with neither organic heart disease nor AF episodes (control group). Programmed electrical stimulation was performed from the right atrium (RA), and the effective refractory period of the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that the index of atrial conduction abnormalities and atrial arrhythmogenesis are substantiated in BS . A shorter action potential duration and steeper restitution curve in the setting of a shorter diastolic interval are observed.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have demonstrated that the index of atrial conduction abnormalities and atrial arrhythmogenesis are substantiated in BS . A shorter action potential duration and steeper restitution curve in the setting of a shorter diastolic interval are observed.…”
Section: Discussionmentioning
confidence: 92%
“…The inducibility of re‐entrant arrhythmias may be dependent on the wavelength of the atrial impulse, considering conduction velocity x refractory period; in particular, when a premature impulse has a short wavelength due to conduction delay or shortened refractoriness, small areas of conduction block may be enough to set up reentrant circuit contributing to the inducibility of AF 57 . These findings may be similar to the pathogenesis of VAs during phase 2 re‐entry.…”
Section: Pathophysiology and Predictors Of Af In Brsmentioning
confidence: 87%
“…Further data are needed to improve the usefulness of noninvasive prognostic markers for identifying high‐risk patients with BrS. The subjects in our study were ≥ 40 years of age, which might reflect a limited scope of this technique. It has been reported that repolarization and depolarization abnormalities in the ventricle in patients with BrS. Kofune et al reported that abnormal interatrial conduction and steep restitution of action potential duration may contribute to the atrial arrhythmogenicity seen in BrS. Noninvasive repolarization markers such as T‐wave alternans or T‐wave variability and electrophysiological markers such as action potential duration should also be investigated.…”
Section: Discussionmentioning
confidence: 99%